Strategi Komunikasi dalam Membangun Konsep Pesantren Karyawan di Pondok Pesantren At-Taqwa Cikarang - Ahmad Agus Salim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Pesantren At-Taqwa Cikarang is often referred to as an employee boarding school, although its students do not only come from employees or workers, but the boarding school is dominated by employees or workers. This research aims to analyse the communication strategy applied by Pondok Pesantren At-Taqwa Cikarang in building the concept of employee boarding school. The main focus of this research is how the communication strategy of Pondok Pesantren At-Taqwa Cikarang in building the concept of employee islamic boarding house. This research uses a qualitative approach with the presentation of descriptive data analysis. The method used in this research is using a case study. This research uses a communication planning model developed by Philip Lesly which consists of organisational components and public components. The results showed that in the organisational component, it was found that the communication strategy used was direct communication and through social media. All students play a role in communication activities and act as communicators. In this component, feedback is marked by the presence of employees who register at Pondok Pesantren At-Taqwa Cikarang. Evaluation activities are carried out if there are employee students who do not want to recite the Koran and by looking at the parameters of likes, comments and subscriptions on social media.